Implementation of Talent Pool System to Realize Professionalism Performance State Civil Apparatus - Oktaviani, Monica; Yuswanto, Yuswanto; Deviani, Eka (Penerbit Goodwood, 2024)
Purpose: Realizing good local government governance and ensuring the availability of professional civil servants require planned and measurable human resource management. Therefore, the Pagar Alam City Government issued Pagar Alam Mayor Regulation No. 24 of 2021 concerning the Policy for Implementing the Civil Servant Talent Pool System within the Pagar Alam City Government. To realize good local governance and ensure the availability of professional civil servants. Method: Normative and empirical methods were employed. Data collection was carried out using field and literature studies. The data analysis was qualitatively descriptive. Result: Implementation of the Talent pool System as a strategy of the Pagar Alam city government to realize the professionalism of the performance of the state civil apparatus, the Pagaralam city government participated in a series of events held at the Regional VII Agency of the State Civil Service Agency (BKN) Palembang by sending 9 (nine) participants. However, the mayor’s regulation has not been fully and maximally realized within the Pagar Alam City government. Limitations: The factors that hinder the implementation of the talent pool system within the scope of the Pagar Alam city government are a lack of human resource participation and budget factors that have not been fully explained. Contribution: Implementation of the Talent pool system as a strategy of the Pagar Alam city government to realize professionalism in the performance of the state civil apparatus.